KNOWLEDGE AND ATTITUDE OF NNAMDI AZIKIWE UNIVERSITY UNDERGRADUATE STUDENTS TOWARDS PRE-MARITAL SICKLE CELL SCREENING - Bosah, Chukwuebuka Nnadozie; Alagbu, Chukwubuikem Eugene (Journal of Early Childhood and Primary Education, 2020)
This study focused on the knowledge and attitude of undergraduate students of Nnamdi Azikiwe University, (NAU) Awka towards sickle cell screening. Two research questions and one hypothesis guided the study. The design of the study was descriptive survey design. Simple random sampling technique by balloting was used to select two faculties from the 13 faculties at Nnamdi Azikiwe University, Awka. Using simple random sampling technique, a sample size of 200 (100 for male and 100 for female undergraduate students) were selected. A well-structured 32 item questionnaire with two clusters was used for collection of data. The instrument was validated by three experts, two from the Department of Human Kinetics and Health Education and one expert from Measurement and Evaluation Unit of Educational Foundation Department both in Faculty of Education, Nnamdi Azikiwe University, Awka. The reliability of the instrument was established using the Cronbach’s Alpha Reliability Coefficient and the reliability obtained on cluster bases were 0.86 and 0.79 respectively. The overall reliability obtained was 0.82. Mean and standard deviation was used to answer research question one, simple percentage was used to answer research question two. T-test was used for the hypothesis at 0.05 level of significance. Findings revealed that both male and female students of the university have good knowledge of the pre-marital sickle cell screening and both male and female have negative attitude towards the screening. The researchers concluded that based on this finding, there is still much work to be done among the undergraduate students in the area of practicing pre-marital sickle cell screening Based on the findings the researchers recommended among others that the issue of creating awareness about sickle cell (SCD) should be a continuous process in the media and in the schools.